Tax and Indonesian Creative Economy - Ratna Septiyanti (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research develops a creative economy model as a strategy to increase tax revenues in Indonesia and to develop theory in the field of taxation in the creative industries sector through empirically testing influence of tax revenues from the creative industries sector on economic growth in Indonesia. The sample used was 8,203,826 creative economy actors in 16 subsectors registered in the Data Center of the Ministry of Tourism and Creative Economy / Tourism and Creative Economy Agency of the Republic of Indonesia on the recent decade. The result provides empirical evidence that there is a significant positive influence of taxes from the creative economy on Indonesian economic growth. The implication of this research is Indonesian government should facilitate the regulation and policy in order to enhance the creative entrepreneurship in Indonesia.